Castles, caves, and honeycombs - Ashman, Linda; Stringer, Lauren (San Diego : Harcourt, 2001)
Describes some of the unique places where animals build their homes such as in a heap of twigs, on a castle tower, in a cave, or in the hollow space inside a tree.
NP
NP
Keywords: Dwellings -- Fiction; Home -- Fiction; Animals -- Fiction; Stories in rhyme